2020
DOI: 10.3390/brainsci10110786
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Social Isolation and Loneliness in Children with Neurodevelopmental Disabilities: A Scoping Review

Abstract: Loneliness and social isolation have negative consequences on physical and mental health in both adult and pediatric populations. Children with neurodevelopmental disabilities (NDD) are often excluded and experience more loneliness than their typically developing peers. This scoping review aims to identify the type of studies conducted in children with NDD to determine the effects of loneliness and/or social isolation. Three electronic databases (Ovid MEDLINE, EMBASE, PsychINFO) were searched from inception un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 61 publications
(143 reference statements)
4
21
0
Order By: Relevance
“…In this view, loneliness is driven by the perceived quality of social relationships and the difficulties in feeling close and connected with social partners, which may be reflected at the neural level by the overlap between self and others' representations (Courtney and Meyer, 2020). Interestingly, feeling disconnected from others can compromise mental and physical health in both neurotypical and clinical groups (Cacioppo et al, 2006;Kwan et al, 2020) and predict the increased mortality even after adjusting for objective social isolation (Cacioppo et al, 2015).…”
Section: Missing the Touch With The Others: The Growing Problem Of Lonelinessmentioning
confidence: 99%
See 2 more Smart Citations
“…In this view, loneliness is driven by the perceived quality of social relationships and the difficulties in feeling close and connected with social partners, which may be reflected at the neural level by the overlap between self and others' representations (Courtney and Meyer, 2020). Interestingly, feeling disconnected from others can compromise mental and physical health in both neurotypical and clinical groups (Cacioppo et al, 2006;Kwan et al, 2020) and predict the increased mortality even after adjusting for objective social isolation (Cacioppo et al, 2015).…”
Section: Missing the Touch With The Others: The Growing Problem Of Lonelinessmentioning
confidence: 99%
“…In this view, loneliness is driven by the perceived quality of social relationships and the difficulties in feeling close and connected with social partners, which may be reflected at the neural level by the overlap between self and others’ representations ( Courtney and Meyer, 2020 ). Interestingly, feeling disconnected from others can compromise mental and physical health in both neurotypical and clinical groups ( Cacioppo et al, 2006 ; Kwan et al, 2020 ) and predict the increased mortality even after adjusting for objective social isolation ( Cacioppo et al, 2015 ). In particular, loneliness has been consistently associated with increased inflammation and higher levels of activation of the hypothalamic-pituitary-adrenocortical (HPA) axis, as reflected by salivary cortisol levels ( Cacioppo et al, 2000 ; Pressman et al, 2005 ) suggesting that perceived social isolation represents an important stressor for humans.…”
Section: Social Connection Through Tactile Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The social and interactive facets of interventions could also protect from mental health issues by preventing loneliness. In fact, while feeling close to other people promotes well-being, feeling disconnected has been shown to compromise mental and physical health—in both neurotypical and clinical samples—thereby strengthening a feeling of neurocognitive isolation [ 47 ].…”
Section: Together Is Bettermentioning
confidence: 99%
“…A study with a rare CNVs analysis by WGS suggested that a de novo deletion that affects TAOK3 (and PEBP1 ) may contribute to schizophrenia (Malhotra et al, 2011 ) and TAOK3 (but not PEBP1 ) was further confirmed in a GWAS analysis (Gilman et al, 2012 ), suggesting LOF of monogenic TAOK3 may contribute to NDDs, at least in schizophrenia. In another GWAS study, TAOK3 was identified as a genetic predisposition to loneliness (Abdellaoui et al, 2019 ), a status that accompanies NDDs (Kwan et al, 2020 ; Papagavriel et al, 2020 ). In addition, two independent GWAS analyses showed that TAOK3 is related to high opioid requirement for patients with advanced cancer pain (Gutteridge et al, 2018 ) and morphine requirement for postoperative pain in a retrospective pediatric day surgery population (Cook-Sather et al, 2014 ), suggesting a functional role of TAOK3 in controlling pain under certain conditions.…”
Section: Clinical Association Between Tao Kinases and Nddsmentioning
confidence: 99%